2018
DOI: 10.1155/2018/3732842
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Increased Zinc Supply against Oxidative Damage of Sublingual Gland in Chronic Exposure to Cadmium: Experimental Study on Rats

Abstract: Cadmium is one of the main chemical pollutants found in the daily environment of developed countries. Cigarettes are a significant source of that metal, which makes it important in terms of oral cavity health. The aim of this study was to determine if increased supply of zinc in chronic exposure to cadmium might protect the sublingual gland structure against oxidative damage. The experiment took 12 months and was conducted on 72 adult male rats. They were randomized into 9 groups. Eight groups received cadmium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 33 publications
(69 reference statements)
0
41
0
Order By: Relevance
“…Recent epidemiological studies provide more and more evidence that environmental exposure to this xenobiotic, nowadays occurring in economically developed countries, creates a threat to the health of the general population, mainly including a risk of damage to the kidney, liver, cardiovascular system, and skeleton, as well as the development of cancer and the deterioration of cognitive functions such as hearing and vision [3,9,13,[15][16][17][18]. It has been revealed that numerous effects of toxic action of cadmium, including the damaging impact on the organs of the oral cavity, result from its pro-oxidative properties [5,14,[19][20][21][22][23]. This xenobiotic indirectly mediates the generation of free radicals (FR) and reactive oxygen species (ROS) by weakening the antioxidative barrier (enzymatic and non-enzymatic), induction of the activity of oxidases, and damage to the mitochondria [3,14,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent epidemiological studies provide more and more evidence that environmental exposure to this xenobiotic, nowadays occurring in economically developed countries, creates a threat to the health of the general population, mainly including a risk of damage to the kidney, liver, cardiovascular system, and skeleton, as well as the development of cancer and the deterioration of cognitive functions such as hearing and vision [3,9,13,[15][16][17][18]. It has been revealed that numerous effects of toxic action of cadmium, including the damaging impact on the organs of the oral cavity, result from its pro-oxidative properties [5,14,[19][20][21][22][23]. This xenobiotic indirectly mediates the generation of free radicals (FR) and reactive oxygen species (ROS) by weakening the antioxidative barrier (enzymatic and non-enzymatic), induction of the activity of oxidases, and damage to the mitochondria [3,14,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Because current environmental exposure to cadmium creates a threat to the health of the general population [3,8,10,11,13,[15][16][17][18] and the lifetime human exposure to this xenobiotic will increase [9][10][11], the attention of researchers in recent years has been focused on finding effective ways to prevent the unfavourable health effects of exposure to this heavy metal. Taking into account the strong pro-oxidative properties of cadmium and the involvement of oxidative stress in the mechanisms of its damaging impact on various organs and systems [3,5,14,[19][20][21][22][23], the greatest interest among the possible protective agents has been paid to natural products characterized by strong antioxidative properties, including polyphenol-rich ones [14,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased zinc has been shown to affect salivary glands. A twelve-month rat study that examined the effect of administering increased levels of zinc on chronic exposure to cadmium, one of the main chemical pollutants in the developed world, found that increased zinc intake had a protective effect on the sublingual gland against oxidative damage with chronic cadmium exposure [53]. However, increased zinc intake should be monitored closely as zinc toxicity has been proven to have a negative effect on the quantity and quality of saliva, probably through changes in neurologic pathways to the salivary glands or effect on the acini cells [54].…”
Section: Role Of Zinc Deficiency In Cleft Lip Cleft Palate and Salivmentioning
confidence: 99%